Factors affecting saving behaviour among online gamers in Greater Jakarta - Farida Komalasari; Dio Julio Sander; Adhi Setyo Santoso; Lukas Sangka Pamungkas (President University, 2022)
Games, especially digital online games in both PC and mobile phones are in its peak of developing and growing. Along with that, the number of gamers significantly increasedfrom every range of age for both men and women. In 2017, the number of gamers in Indonesia are 43.7million people, which increased to 52 million people in 2019. Contradicting the growth of gamers, Indonesians’ intention to save is low compared to other countries in ASEAN. Considering this phenomena, this paper aims to investigate the factors that affects saving behaviour of online gamers in Indonesia, especially in Greater Jakarta. This is a quantitative research using primary data from 218 respondents. The respondents are selected using non-probability sampling that are purposive sampling and snowball sampling. The data were gathered using questionnaire, whuch consists of demographic variables and 41 statements as variable measurementsdistributed to online gamers in Greater Jakarta, Indonesia. The data were analyzed using Structural Equation Model (SEM). A research found that financial literacy significantly influences both financial attitude and saving behaviour of online gamers in Greater Jakarta, Indonesia. The financial attitude also significantly influences their saving behaviour. Meanwhile, family influence and peer influence do not significantly influence their saving behaviour. Authors believe that this is the first research in Indonesia using this framework with online gamers as its object of research.